Not a First Language but One Repertoire: Translanguaging as a Decolonizing Project. (August 2022) - Wei, Li; García, Ofelia
Translanguaging has opened up spaces to recognize the dynamic multilingualism of students in classrooms taught in dominant languages, and problematized concepts such as 'additive bilingualism'. This article aims to further explore two issues that remain little understood. First, translanguaging is often seen as simply the acknowledgement or use of multilingual students' 'first language'. This article clarifies that this is a misunderstanding, for the trans- in translanguaging connotes the transcendence of named languages, the going beyond named languages as have been socially constructed. Second, in going beyond named languages, translanguaging is also intended as a decolonizing project, revealing how bilinguals inhabit a world with different knowledge bases and linguistic/cultural practices. We use two bilingual students, in London and New York City respectively, to show how they are viewed and listened to by their teachers as bilinguals with two 'incomplete' linguistic systems because each element in their language/semiotic repertoire is seen as a separate entity. We then weave all the elements together to provide a fuller picture of these students. In doing so, we reject raciolinguistic ideologies that have enregistered them as deficient and instead regard them through a translanguaging lens. The article emphasizes the importance of understanding translanguaging as a unitary repertoire, as well as its decolonial potential in education as teachers abandon the focus on named standardized languages and engage fully with their students' full repertoire of features and meanings.